2009
DOI: 10.1103/physrevd.79.065001
|View full text |Cite
|
Sign up to set email alerts
|

Stability of false vacuum in supersymmetric theories with cosmic strings

Abstract: We study the stability of supersymmetry breaking vacuum in the presence of cosmic strings arising in the messenger sector. For certain ranges of the couplings, the desired supersymmetry breaking vacua become unstable against decay into phenomenologically unacceptable vacua. This sets constraints on the range of allowed values of the coupling constants appearing in the models and more generally on the chosen dynamics of gauge symmetry breaking.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In a recent paper [21], we had emphasized that it is not sufficient to study the stability of supersymmetry breaking vacua in terms of their translation invariant form alone. In general, topological defects can form in the evolution of the early universe [22].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper [21], we had emphasized that it is not sufficient to study the stability of supersymmetry breaking vacua in terms of their translation invariant form alone. In general, topological defects can form in the evolution of the early universe [22].…”
Section: Introductionmentioning
confidence: 99%
“…Some relevant studies have been carried out in Refs. [36,37]. In this paper, we study in detail the structure of the R-string/tube solution in SUSY models.…”
mentioning
confidence: 99%
“…In [10], we investigated the various aspects of the R-tube and found that there can be light unstable modes. In these reasons, a gauge mediation model with spontaneously broken R-symmetry is an ideal example to demonstrate implications of such complicated vacua in a realistic situation (see [39,40] for relevant earlier works).…”
Section: Jhep05(2013)091mentioning
confidence: 99%